The New Specialties of Orofacial Pain and Oral Medicine: Practical Strategies to Improve Access to Care for Orofacial Disorders - James Fricton; Nelson L. Rhodus (Journal of the California Dental Association)
Orofacial disorders are common and complex disorders with an estimated collective prevalence of over 40% of the general population. To improve access to care, orofacial pain and oral medicine have now been recognized as dental specialties. Thus, it is recommended that all dental schools and other health professional schools increase pre- and post-doctoral education, patient care, clinical training, and research on these conditions. This paper reviews the barriers and solutions to improving access to quality, effective, and affordable care for oral and facial disorders to prevent complications, chronic pain and the negative impact on the lives of those who suffer from them.